Research Progress in Traditional Chinese Medicine Treatment for Post-stroke Spastic Hemiplegia - Gu, Yu; Ding, Tianhong (Journal of Contemporary Medical Practice, 2026)
Stroke is an acute cerebrovascular circulatory disorder with sudden onset, caused by various inducing factors that lead to stenosis, occlusion, or rupture of the cerebral arteries. Its clinical manifestations are primarily characterized by sudden syncope, loss of consciousness, or abrupt occurrence of facial deviation, hemiplegia, stiff tongue with dysphasia, and intellectual impairment. Stroke can result in motor dysfunction, with spastic hemiplegia being the most common condition, severely affecting the patient’s quality of life and work capacity. This article reviews recent advances in Traditional Chinese Medicine (TCM) research on post-stroke spastic hemiplegia. By elucidating various treatment modalities and conducting a comprehensive analysis of their outcomes, this review aims to better serve patients and enhance their quality of life.